Total Suspends Mozambique LNG Temporarily on Security Threat - Francois De Beaupuy; Paul Burkhardt; Borges Nhamirre (Bloomberg.com, 2021)
French energy giant Total SE suspended its $20 billion liquefied natural gas project in Mozambique indefinitely due to an escalation of violence in the area, including a March attack by Islamic State-linked militants.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mulheres denunciam corrupção nas maternidades de Nampula - Voa Português (Voa Português, 2015)
Parteiras exigem entre 500 e 2.000 meticais para realizar partos. Cobranças ilícitas nas maternidades das unidades sanitárias em Nampula, Moçambique, estão a comprometer a qualidade do atendimento materno-infantil e a “forçar” as grávidas a optarem por ter filhos na comunidade. Algumas mulheres ouvidas pela VOA no Hospital Central de Nampula denunciaram o mau atendimento nas unidades sanitárias. Acusam ainda profissionais de cobrarem entre 500 e 2.000 meticais para realizar um parto.
Keywords: G - Mozambique / Moçambique; GP - Nampula; L - portuguese / português; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Organizações não-governamentais denunciam mau atendimento das parturientes nas unidades sanitárias - Joana da Lúcia (CanalMoz, 2021)
Em protesto contra a violência e tratamentos degradantes nas unidades sanitáriasno período pré-natal, de parto, e pós-natal, em todo o país, quarenta organisações não-governamentais reuniram-se na terça-feira, 12 de outubro, para exigir a resposabilização administrativa e criminal das profissionais de saúde que atendem essas mulheres nos hospitais.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde